Articulations of power: Guns on campus and the protests against them - Butters Albion M. (The Finnish Anthropological Society, 2025)
When carrying concealed handguns on campus was legalised at The University of Texas (UT) at Austin in 2015, students and faculty positioned themselves in relation to the new law in very different ways, ranging from large demonstrations and the use of various types of rhetoric to non-vocal representations and deliberate silence. This essay examines an important transitional moment in the educational environment by focusing on the respective relationships and modes of expression—or articulations—of the affected parties regarding the issue of firearms on university premises, as these reflected opposing camps within the academic community. Drawing on interviews and quantitative research, and proposing a novel theoretical frame to understand the complex subject of guns, this essay examines the polemics, polarisation, and power dynamics around Campus Carry at UT Austin.